MANET Cluster Optimization Using ILP/SAT Techniques - Zahidi, Syed Zohaib Hussain (2012)
A Master of Science thesis in Computer Engineering by Syed Zohaib Hussain Zahidi entitled, "Manet Cluster Optimization Using ILP/SAT Techniques," submitted in January 2012. Thesis advisor is Dr. Fadi Ahmed Aloul and co-advisor is Dr. Assim Sagahyroon. Available are both soft and hard copies of the thesis.